EFFICACY, SAFETY AND COMPLIANCE OF TERAZOSIN IN THE TREATMENT OF PATIENTS WITH SYMPTOMATIC BENIGN PROSTATIC HYPERPLASIA. - Jafri, Syed Saleem Abbas; Akhter, Muhammad Saleem; Ahmad, Mumtaz; Hussain, Sajjad (Journal of Ayub Medical College Abbottabad, 2000)
Background: The primary objective of this study was to determine the efficacy, safety and compliance of terazosin, a selective long-acting alpha 1-blocker, for the treatment of symptomatic BPH. Methods: A total of 150 patients ranging in age between 45 and 81 years with symptomatic BPH were included. They were randomly assigned to receive terazosin (n =74) or placebo (n = 76) for 12 weeks. Results: Terazosin significantly improved urinary symptoms versus placebo, assessed by using the 1-PSS (-30vs. -17%, P=0.007). Maximum flow rate increased significantly with terazosin (2.3 ml/s i.e. ± 28%) compared with placebo (1.1 ml/s i.e. ±13%, P=0.006). Residual urine was also significantly reduced with terazosin. Overall, terazosin was as well tolerated as placebo. Seven patients were withdrawn from the study for adverse events with terazosin (9.45%) and eight patients (10.52%) with placebo. The incidence of vasodilatation-related events like postural symptoms, dizziness, headache with terazosin was similar (8.11%) to that of placebo (7.90%). The reduction in supine blood pressure was minor (< 5mm Hg), both in normotensive and hypertensive patients. Conclusion: This study demonstrates the efficacy, safety and compliance of terazosin for the treatment of BPH.